Meningkatkan Minat Belajar Anak Usia Dini 5-6 Tahun Melalui Media Film Animasi Pembelajaran Di TK Negeri Pembina 1 Medan - Purba, Sondang; Yetti Rosmawati Pangaribuan; Jainatun Naimah; Antonius Wilson Sembiring; Lusiana Ririn Manao (Universitas Sari Mutiara Indonesia, 2024)
This research was conducted to increase interest in learning in children aged 5-6 years through the medium of animated learning film at the pembina 1 kindergarten in medan. Subjects in this were children aged 5-6 years who were in group B totaling 16 children. This research is a classroom action research with a quantitative descrptive approach. Data collection techniques used in this study are observation and documentation. Based on the result of the research, it shows that there has been an increase in children interest in learning through learning as animated film media in gruop B at the Pembina 1 Kindergarten in Medan. This is proven by the pre-cycle result of 27,25%, then in the first cycle it was 41,6% and increased to 87,75% in the second cycle. So it can be conculed that the activity of watching animated learning film media can increase children interest in learning in the pembina state kindergarten 1 Medan.